Influences of Microwave Irradiation on the Physicomechanical Properties and Cerchar Abrasivity Index of Rocks - Gaoming Lu; Cong Ding; Kairong Hong; Jianjun Zhou; Haining Liu; Changbin Yan (Geofluids)
The research is aimed at exploring the influences of microwave irradiation on the physicomechanical properties and Cerchar abrasivity index (CAI) of rocks. For this purpose, basalt collected in Chifeng (the Inner Mongolia Autonomous Region, China) was taken as research objects to carry out microwave irradiation tests for different durations in a multimode cavity. By using the MTS815 mechanical testing machine and the abrasion servo tester of rocks, mechanical tests and Cerchar abrasion tests were conducted before and after microwave irradiation. Changes in the mass, volume, surface fractures, surface temperature, ultrasonic wave velocity, uniaxial compressive strength (UCS), and CAI of the basalt samples before and after microwave irradiation were analyzed. Results show that the surface temperature of basalt samples linearly increases with the duration of microwave irradiation. The volume and fracture coalescence of the rock samples both increase with the prolonging duration of microwave irradiation. The mass, ultrasonic wave velocity, UCS, and CAI of the basalt samples all decrease with the increase in the duration of microwave irradiation. The reduction of the physicomechanical properties and CAI of rocks indicates that microwave irradiation can reduce the wear of rock-breaking tool and thus improve the efficiency of rock breaking.